Lean and eco-efficient method for evaluating the potency of tinidazole in tablets - Pollyanna Barbara Henrique; Ieda Sapateiro Torres; Ana Kogawa (Drug Analytical Research)
Tinidazole (TIN), an amoebicide and giardicide, does not present microbiological methods in official compendia for evaluating the potency of final products. The objective of this work is to develop and validate an effective, lean and eco-efficient microbiological turbidimetric method by National Environmental Method Index (NEMI) and Eco-Scale Assessment (ESA) to evaluate the potency of TIN-based tablets. The microbiological method was performed using Escherichia coli ATCC 25922 at 1 % in BHI broth, TIN solution in purified water and ethanol (90:10, v/v) at concentrations of 40, 60 and 90 μg mL-1, shaker at 80 rpm, 4 hours of incubation, quartz cuvette and 530 nm. The method was linear from 40 to 90 μg mL-1 with a correlation coefficient of 0.9991, selective, precise (RSD < 4 %), accurate with 99.65 % recovery and robust to changes in culture medium volume, culture medium brand, inoculum percentage and shaker rotation speed. The potency of TIN tablets was 98.50 %. The greenness of the method was evaluated and NEMI presented 3 green quadrants and the ESA score was 93, showing an excellent green analysis option. This work presents a lean and eco-efficient proposal for evaluating the potency of TIN tablets for chemical-pharmaceutical laboratories around the world.